Identifying the most important research, policy and practice questions for substance use, problematic alcohol use and behavioural addictions in autism (SABA-A): A priority setting partnership - Sinclair, J.M.A.; Aslan, B.; Agabio, R.; Anilkumar, A.; Brosnan, M.; Day, E.; Dowling, N.A.; Flood, C.; Grant, J.E.; Halliday, R.; Hofvander, B.; Howes, L.; et al. (2023)
Background: Autistic people are more likely to report problematic alcohol and other substance use when compared to the general population. Evidence suggests that up to one in three autistic adults may have an alcohol or other substance use disorder (AUD/SUD), although the evidence base for behavioural addictions is less clear. Autistic people may use substances or engage in potentially addictive behaviours as a means of coping with social anxiety, challenging life problems, or camouflaging in social contexts. Despite the prevalence and detrimental effects of AUD, SUD and behavioural addictions in community samples, literature focusing on the intersection between autism and these conditions is scarce, hindering health policy, research, and clinical practice. Methods: We aimed to identify the top 10 priorities to build the evidence for research, policy, and clinical practice at this intersection. A priority-setting partnership was used to address this aim, comprising an international steering committee and stakeholders from various backgrounds, including people with declared lived experience of autism and/or addiction. First, an online survey was used to identify what people considered key questions about Substance use, alcohol use, or behavioural addictions in autistic people (SABA-A). These initial questions were reviewed and amended by stakeholders, and then classified and refined to form the final list of top priorities via an online consensus process. Outcomes: The top ten priorities were identified: three research, three policy, and four practice questions. Future research suggestions are discussed.